Efek LKS IPA terpadu tema gerak dalam kehidupan sehari-hari bermuatan keterampilan literasi dalam pendekatan saintifik pada hasil belajar siswa kelas VIII SMPN 25 Padang - Meisyarah Nabillah; Asrizal Asrizal; Festiyed Festiyed; Syafriani Syafriani (PILLAR OF PHYSICS EDUCATION, 2019)
The 21st century is marked by the rapid progress of knowledge, information and communication and technology. To develop the some abilities of students in the 21st century, they must have good the literacy skills. The government has encouraged literacy skills of students through the school literacy program. Besides that, the government also has tried to improve learning outcomes of students through integrated science teaching. However, the real condition indicated that the integration of science learning material in schools was still low. The average value of integration of the science learning material in the student worksheet which used in the Padang city was 53.87. The solution to this problem is to implement the integrated science student worksheet by integrating the literacy skills. The purpose of the research was to determine the effect of the use of the integrated science student worksheet on the theme of motion in daily life by integrating literacy skills in the scientific approach to the learning outcomes of grade VIII students in SMPN 25 Padang. The type of research was a quasi-experimental with Randomized Control-Group Only Design. The sampling technique used both purposive sampling and cluster random sampling. The instrument for collecting the data on learning outcomes of students consists of three parts, namely the attitude observation sheet for the attitude aspect, the knowledge test sheet in the form of a post test for the knowledge aspect, and the scientific performance assessment sheet for the skill aspect. The research data were analyzed by using descriptive statistics, normality test, homogeneity test and comparison test of two means. Based on data analysis, it can be stated that the use of the integrated science student worksheet on the theme of motion in daily life by integrating the literacy skills in the scientific approach has a significant effect on student learning outcomes on aspects of knowledge, skills, and attitudes with a 95% confidence level. This result also indicated that the integrated science student worksheet on the theme of motion in daily life by integrating the literacy skills in the scientific approach is effectively used in science teaching by science teachers for grade VIII students.